"Bis auf den Punkt der Liebe": The Phantasmagorical Image of the Small in Anton Reiser. (1st October 2016) - Arribas, Sonia
Abstract : This essay proposes a reading of Karl Philipp Moritz's Anton Reiser, focusing on the two component elements of its fundamental "Symbolik" (this is the standard translation of Goethe's "das Symbolische" as used by Walter Benjamin when discussing works of art): material content and truth content. The first is approached via commentary, the second through an interrogation of the novel's central enigma. Regarding material content, the essay discusses three quotations from Moritz selected by Benjamin in one of his radio 'Hörmodelle'. I argue that these instantiate the novel's 'Symbolik', and I call this the 'phantasmagorical image of the small'. It manifests itself in the recurring motif of adventure and wandering, in the way the novel depicts the role of the imagination, and in the form in which it addresses the question of Reiser's destiny. Regarding truth content, I concentrate first on a small but crucial detail. Reiser identifies with Werther in all ways except one, radically excluding the possibility of a love encounter. Anton Reiser 's enigma of the small is condensed in a phantasmagoria without any love-object. Second, I delineate the novel's denouement in order to show that Anton Reiser offers, avant la lettre, a perspective on modernity alternative to that of the classic Bildungsroman.